Comparison of Three Protocols to Preserve Leptospira spp. in Cat Urine for Efficient DNA Extraction and PCR Amplification - Cordeiro, Carolina Trochmann; Marinho Valente, Jéssica Damiana; dos Santos, Leonardo Gaspareto; da Costa Vieira, Rafael Felipe; Jayme Vieira, Thálitha Samih Wischral; de Oliveira Stedile, Simone Tostes (Acta Scientiae Veterinariae, 2019)
Background: The pathogenic leptospira infection in mammalian species can cause a range of acute or chronic manifestations and may result in a carrier state. Previous studies have suggested that cats were resistant to acute leptospirosis however, the description of some clinical cases suggests that Leptospira spp. may also be pathogenic to this species. Recent studies have shown that leptospires may be shed in the urine of infected cats. Endogenous substances present in urine may inhibit PCR and allow leptospires to evade detection. This study aims to compare three protocols for sample processing to optimize the detection of pathogenic leptospires in cat urine. Materials, Methods & Results: Three protocols to optimize the detection of pathogenic leptospires in cat urine were tested. Aliquots of standard concentration of L interrogans serovar Canicola culture were added to urine samples to achieve concentrations of 1×105 to 1×102 leptospires/mL for each protocol. In protocols A and B the urine was neutralized by the addition of phosphate-buffered saline (PBS), pH 7.4, in a proportion of 1 PBS: 2.5 urine (v/v). In protocol A, PBS was added to neutralize the urine pH for the leptospiral organisms immediately after addition of leptospires. In protocol B, PBS was added just before DNA extraction. In protocol C, no PBS was added. DNA extraction was performed at 4, 24 and 48 h after addition of the leptospires using a modified protocol. Samples were incubated at 37ºC for 10 min. Samples were then centrifuged (850 g) for 15 min, at 25ºC. The supernatants were transferred to another tube, and the pellets were discarded. The supernatants were centrifuged (16060 g) for 20 min at 4ºC. The supernatants were then discarded, and the pellets resuspended and washed with 1000 µL of PBS. All the samples were centrifuged at 16060 g for an additional 20 min at 25ºC. The supernatants were discarded and the pellets were resuspended in 100 µL of PBS and incubated at 94ºC for 10 min. DNA was stored at -20ºC until the molecular analysis. The PCR detection limit was evaluated. In samples from protocol A, leptospires were detected in concentrations up to 1×103 (4 h) and 1×104 (24 and 48 h). In protocol C, leptospires were detected in concentrations up to 1×104 (4 h) and 1×105 (24 and 48 h). No leptospiral DNA was detected in samples from protocol B. Discussion: Leptospires are sensitive to acid conditions, at pH 6.8 or lower and the urine pH of cats may vary from 5 to 7. In the present study, we found best results for DNA amplification with the addition of PBS immediately after urine collection (protocol A). Previous studies have shown the importance of neutralizing urine samples immediately after collection to avoid loss of bacterial DNA during the extraction process. However, protocols B and C may be an alternative in clinical practice, when PBS cannot be added immediately after collection. The delay after urine collection before DNA extraction is one more factor that may interfere with the PCR sensitivity. This was observed in the samples from protocol A, because although these samples were neutralized immediately, there was a 10-fold decrease in the detection limit of the test at 24 and 48 h. Leptospires rapidly lose their integrity in urine and the detection limit declines considerably over time, so prompt extraction is essential. These results show that the in-house method of preserving cat urine is useful to maintain the viability of leptospiral DNA extraction. In addition, this study highlights the importance of neutralizing urine samples immediately after collection and the need for prompt DNA extraction to improve PCR detection limit. However, if PBS cannot be added to the collected sample immediately, it is better to process the sample without PBS and extract DNA as soon as possible to minimize the risk of false-negative results.